2020
DOI: 10.1071/rd20112
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet leads to elevated lipid accumulation and endoplasmic reticulum stress in oocytes, causing poor embryo development

Abstract: The present study was designed to investigate the effect of diet-induced obesity on endoplasmic reticulum (ER) stress in oocytes. Swiss albino mice (3 weeks old) were fed with a high-fat diet (HFD) for 8 weeks. Oocytes were assessed for lipid droplet accumulation, oxidative stress, ER stress and their developmental potential invitro. High lipid accumulation (P<0.01) and elevated intracellular levels of reactive oxygen species were observed in both germinal vesicle and MII oocytes of HFD-fed mice (P&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…L-carnitine added in the IVM medium increases follicular β-oxidation levels, thus improving the fertilization rate and blastocyst formation rate ( Dunning et al, 2011 ). On the other hand, long-term exposure to a high-fat environment increases lipid levels in oocytes of women with obesity or polycystic ovary syndrome (PCOS) and induces lipotoxicity in oocytes, including the increase in oxidative stress and inflammation levels and disruption of spindles and chromosome structure, thus seriously interfering oocyte meiosis ( Hou et al, 2016 ; Yun et al, 2019 ; Rao et al, 2020 ). Previous studies showed that the developmental potential of oocytes growing in follicular fluid with high content of stearic acid, palmitic acid, or oleic acid has decreased significantly ( Valckx et al, 2014 ).…”
Section: Effects Of Lipid Metabolism On Oocyte Maturationmentioning
confidence: 99%
“…L-carnitine added in the IVM medium increases follicular β-oxidation levels, thus improving the fertilization rate and blastocyst formation rate ( Dunning et al, 2011 ). On the other hand, long-term exposure to a high-fat environment increases lipid levels in oocytes of women with obesity or polycystic ovary syndrome (PCOS) and induces lipotoxicity in oocytes, including the increase in oxidative stress and inflammation levels and disruption of spindles and chromosome structure, thus seriously interfering oocyte meiosis ( Hou et al, 2016 ; Yun et al, 2019 ; Rao et al, 2020 ). Previous studies showed that the developmental potential of oocytes growing in follicular fluid with high content of stearic acid, palmitic acid, or oleic acid has decreased significantly ( Valckx et al, 2014 ).…”
Section: Effects Of Lipid Metabolism On Oocyte Maturationmentioning
confidence: 99%
“…If the function of ribosomes is damaged during ovary organization and oogenesis in phreodrilid clitellate, it can bring about oocyte dysfunction or abnormal fertilization ( Witek et al, 2020 ). The expression of endoplasmic reticulum stress-related proteins in mouse oocytes increased in obese mice, which led to the decrease in mouse oocyte quality and embryo development ( Rao et al, 2020 ). The disruption of cis-Golgi apparatus marker protein GM130 causes the decrease in the polar body rate and the quality of mouse oocytes (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Oocyte quality is essential for female fertility and offspring health, and the developmental environment of the maturing oocyte is essential for optimal oocyte quality. An obesogenic diet, for example, has been shown to alter the reproductive function and offspring health by changing the biochemical environment of the follicle and inducing endoplasmic reticulum stress, telomere dysfunction [ 122 ], mitochondrial dysfunction, oxidative stress, and lipid droplet accumulation [ 123 ].…”
Section: Beyond Epigenomementioning
confidence: 99%